THE INFLUENCE OF ISLAMICITY PERFORMANCE INDEX, INTELLECTUAL CAPITAL, AND PROFITABILITY ON ISLAMIC SOCIAL REPORTING DISCLOSURE IN ISLAMIC COMMERCIAL BANKS IN INDONESIA IN THE PERIOD 2016-2018 - Aulia Nurmala Fitriani; Ely Windarti Hastuti (University of Darussalam Gontor, 2021)
Abstract: Indonesian Islamic financial institutions, especially Islamic banking are experiencing increasingly rapid growth. Islamic financial institutions set the Islamic social reporting index as an effort to balance economic and spiritual activities in Islamic banking activities. Therefore, it is important for Indonesian Islamic banking to improve performance, not only from the economic aspect but also from the spiritual aspect. Islamic Social Reporting is a measure of social performance that can align between economic and spiritual aspects in Islamic banking activities. Several ratios can be used to make measurements on the Islamic social reporting index, namely the Islamic performance index, intellectual capital, and profitability The study aim to analyse the effect of the Islamicity Performance Index, Intellectual Capital, and Profitability variables on the disclosure of Islamic Social Reporting at Islamic Commercial Banks in Indonesia. The sample used was 14 Sharia Commercial Banks in Indonesia in the 2016-2018 period. This research used quantitative approach with panel data regression as an analysis. The results of this study indicate that partially the Islamicity Performance Index variable does not have a significant positive effect on Islamic Social Reporting. But the Intellectual Capital and Profitability variables have a significant positive effect on the disclosure of Islamic Social Reporting.Keywords: Islamicity Performance Index, Intellectual Capital, Profitability, Islamic Social Reporting